2019
DOI: 10.3389/fenvs.2019.00172
|View full text |Cite
|
Sign up to set email alerts
|

Soil Aggregates as a Source of Dissolved Organic Carbon to Streams: An Experimental Study on the Effect of Solution Chemistry on Water Extractable Carbon

Abstract: Over the past two decades, headwater streams of the northern hemisphere have shown increased amounts of dissolved organic carbon (DOC), coinciding with decreased acid deposition. The exact nature of the mechanistic link between precipitation composition and stream water DOC is still widely debated in the literature. We hypothesize that soil aggregates are the main source of stream water DOC and that DOC release is greater in organic rich, riparian soils vs. hillslope soils. To test these hypotheses, we collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 61 publications
1
28
2
Order By: Relevance
“…The increase in organic matter solubility in the O horizon has been attributed to increased pH [26], but may be more a function of decreased ionic strength, which has also occurred with decreased deposition levels. In that process, pH increases in the lower pH soils could be driven by increased H + consumption by weak organic anions exposed as organic matter disaggregated [49]. In essence, the relationships of initial O horizon pH to pH and exAl recovery indices are coupled, based on chemical changes in this horizon resulting from reduced deposition.…”
Section: Discussionmentioning
confidence: 99%
“…The increase in organic matter solubility in the O horizon has been attributed to increased pH [26], but may be more a function of decreased ionic strength, which has also occurred with decreased deposition levels. In that process, pH increases in the lower pH soils could be driven by increased H + consumption by weak organic anions exposed as organic matter disaggregated [49]. In essence, the relationships of initial O horizon pH to pH and exAl recovery indices are coupled, based on chemical changes in this horizon resulting from reduced deposition.…”
Section: Discussionmentioning
confidence: 99%
“…SOC decomposition and DOC production have been studied extensively (Abbott et al, 2015;Hale et al, 2015;Humbert et al, 2015;Lambert et al, 2013;Neff and Asner, 2001), yet the interactions between SOC and DOC and their response to climate change at catchments or larger scales remain unresolved (Laudon et al, 2012;Clark et al, 2010). Some regions have experienced long-term increases in DOC, potentially due to recovery from acid rain or climate-induced changes in temperature (T ) and hydrological flow (Laudon et al, 2012;Perdrial et al, 2014;Evans et al, 2012;Monteith et al, 2007), whereas others have observed decreases or no change (Skjelkvale et al, 2005;Worrall et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Transfer by DOC decreased substantially after year 10, from 5.9 g C m -2 y -1 in the 10 th year to 0.09 g C m -2 y -1 at the 26 th year due to a reduction in CWD decomposition. The DOC incorporated into soils can be absorbed or aggregated and therefore maintained in soils for a longer time [55,56]. These simulation results provide context for suggesting the magnitude of the transfers of C from CWD into the soil.…”
Section: Plos Onementioning
confidence: 77%